Inspection of the strength of the column lattice of the improved fiber cleaner - Rakhimov, Rashid; Sultonov, Mirzaolim (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this article, the strength testing of the combed wire mesh, which constitutes an improved cotton fiber cleaning device, was carried out in the Solid Works program. As a result, it was found that the minimum strength reserve of the combed wire mesh is sufficiently high, so the probability of structural failure or plastic deformation in the model is very low.